Mapping the 4D lithospheric architecture of Zealandia using zircon O and Hf isotopes in plutonic rocks - Turnbull, Rose E.; Schwartz, J. J.; Fiorentini, M. L.; Klepeis, K. A.; Jongens, R.; Miranda, E.; Evans, N. J.; Ludwig, Thomas; Waight, T.; Faure, K.; McDonald, B. J. (Gondwana research, 2023)
In this contribution, we examine the crustal architecture of a Phanerozoic Cordilleran margin along a segment of the former Gondwana supercontinent. The Zealandia Cordillera, active at c. 500 - 100 Ma, is characterized by magmas that were emplaced throughout the entire crustal column and exhibit variable whole-rock and zircon stable and radiogenic isotopic compositions. Using new and existing in-situ zircon 206Pb-238U, δ18O and Lu-Hf data for 266 plutonic rocks, we create multi-isotope contour maps that are shown to effectively delineate lithospheric architecture. Importantly, we demonstrate that O and Hf isotope contour maps, in combination with 206Pb-238U age control and published structural mapping, can help identify long-lived, deep-seated crustal structures that influenced the composition and location of magmatism, as well as facilitated and focused past and recent deformation and faulting. We also present isotopic binary mixing models for the entire history of Phanerozoic magmatism along the Zealandia Cordillera. Isotopic mixing models are consistent with mixing of various supracrustal, primitive lower crustal plutonic, and arc mantle sources, each with diverse ages and compositions. Mixing models support several episodes of major net-crustal growth and recycling. The isotopically defined crustal domains (including a distinct light δ18O value Eastern Isotope Domain) vary in size and composition from the Paleozoic - Mesozoic, suggesting that while lithospheric architecture had some influence on magmatism and related mineralization, lower-plate processes and their associated arc-tectonic geometry has also had a significant role in controlling magma compositions, and importantly the volume and flux of magmatic ‘flare-up’ events. Finally, published zircon O and Hf isotope data along the former southeast Gondwana margin enables strong correlations and comparisons across the now separated continental landmasses. The recognition of Permian rocks in Marie Byrd Land with light δ18O values support previous correlations between Zealandia’s outboard Median Batholith and the Amundsen Province.